Feminist resistance and the fight for the life in the pandemic - Gómez, Ginneth Pulido Gómez; Correa, Jessica Aparecida; Viana Alves, Priscila (Geografares, 2021)
A conversation round with two women (Marcia Palhano, Pastoral Land Commission/ Maranhão and Lida Bejarano, base team Warmis - Convergence of cultures) brought up the female role in the first line of combat against the COVID-19 pandemic, affirming that the fight is for life and for dignified conditions to (re) exist in the midst of a scenario of uncertainty, in which, various structural violences - but not new ones - were exacerbated. This article discusses some problems derived from the capitalist system and its racist and patriarchal practices on women’s bodies, understanding that resistance to said system and the proposals for renewal are urgent to preserve life. Thus, the importance of social movements, the defense of territories, solidarity networks and the urgency of alternatives in relations with nature, stand out in this period of epidemiological, social, political and economical crisis.